Patient Satisfaction with the Endoscopy Experience and Willingness to Return in a Central Canadian Health Region - Russell Loftus; Zoann Nugent; Lesley A Graff; Frederick Schumacher; Charles N Bernstein; Harminder Singh (Canadian Journal of Gastroenterology)
OBJECTIVE: Patient experiences with endoscopy visits within a large central Canadian health region were evaluated to determine the relationship between the visit experience and the patients’ willingness to return for future endoscopy, and to identify the factors associated with patients’ willingness to return.